2023
DOI: 10.1029/2022jd037924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Typhoon In‐Fa (2021) and the Western Pacific Subtropical High on an Extreme Heavy Rainfall Event in Central China

Abstract: Heavy rainfall events (HREs) have great socioeconomic impacts around the world and cause deadly and destructive disasters. China is located in the East Asia monsoon area and frequently susceptible to heavy rainfall and flooding extremes (Cao & Gao, 2007;H. Li et al., 2017). Studies on HREs have always been concerned widely and highly (Chen et al., 2012;Junker et al., 1999).Although HREs generally have a short-lived and localized nature (Jo et al., 2020), they are actually modulated by synoptic-scale systems, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This blocking effect can increase the convergence of moist air, intensifying precipitation processes [29][30][31]. Rao et al found that the coupling effect of typhoons and WPSH played an important role in the July 2021 Zhengzhou, Henan extreme rainfall [32].…”
Section: Data Sources and Processingmentioning
confidence: 99%
“…This blocking effect can increase the convergence of moist air, intensifying precipitation processes [29][30][31]. Rao et al found that the coupling effect of typhoons and WPSH played an important role in the July 2021 Zhengzhou, Henan extreme rainfall [32].…”
Section: Data Sources and Processingmentioning
confidence: 99%
“…The average accumulated precipitation over Zhejiang Province was 191 mm [23] as a result of the slow movement in Hangzhou Bay for 16 h, breaking the record for total typhoon landfall precipitation in Zhejiang. The early stages of In-Fa supplied a tremendous amount of moisture to central China, contributing to the 21.7 heavy rainfall event in Henan Province [24,25].…”
Section: Description Of Typhoon In-fa (2021)mentioning
confidence: 99%
“…China's coastal regions are struck by an average of seven typhoons each year. These typhoons can cause meteorological calamities such as storm surges and severe convective weather, which can have a significant impact on residents of coastal and adjacent areas [3][4][5]. The track errors may lead to an accuracy decrease of weather event predictions.…”
Section: Introductionmentioning
confidence: 99%